Enhancing Subjective Well-Being in Taiwanese University Students Through an Eight-Week Mindfulness-Based Program: A Pilot Study - Li-Jen Lin; Su-Ping Yu; Yu-Hsun Lin; Yi-Lang Chen (Behavioral Sciences)
While mindfulness has demonstrated extensive benefits across diverse populations, research on its integration as a formal course and its effects on subjective well-being (SWB), particularly among Taiwanese university students, remains limited. This pilot study examined changes in SWB among 85 Taiwanese university students (61 males, 24 females) following an 8-week Mindfulness-Based Cognitive Therapy for Life (MBCT-L) course. Participants included 38 lower-grade (pre-internship) and 47 senior (post-internship) students. SWB was measured using the 29-item Oxford Happiness Questionnaire (OHQ), rated on a 6-point Likert scale, and administered before and after the intervention. Results revealed a significant increase in students’ overall SWB scores from 3.69 to 3.92 post-intervention. Although females initially exhibited higher baseline SWB compared to males, no significant sex differences were observed after the course. Score discrepancies between pre- and post-test stages varied across sex and internship status, indicating differential impacts of the MBCT-L course on distinct demographic groups. Additionally, this study validated the reliability of the short version of the OHQ (8 items) for use in similar research contexts. By conducting a formal MBCT-L course for Taiwanese university students, this study provides valuable empirical evidence, contributing to the cross-cultural understanding of mindfulness-based interventions and their effects on SWB.